1996
DOI: 10.1029/95jd03352
|View full text |Cite
|
Sign up to set email alerts
|

Validation of O(1S) wind measurements by WINDII: the WIND Imaging Interferometer on UARS

Abstract: This paper describes the current state of the validation of wind measurements by the wind imaging interferometer (WINDII) in the O(1S) emission. Most data refer to the 90‐to‐110‐km region. Measurements from orbit are compared with winds derived from ground‐based observations using optical interferometers, MF radars and the European Incoherent‐Scatter radar (EISCAT) during overpasses of the WINDII fields of view. Although the data from individual passes do not always agree well, the averages indicate good agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 19 publications
4
68
0
Order By: Relevance
“…Over a 14-year period the space-borne high-resolution Doppler imager (HRDI) (Burrage et al, 1996) measured wind velocities typically between 60 • N and 60 • S and down to 50 km and contributed to the Upper Atmosphere Research Satellite (UARS) Reference Atmosphere Project (URAP) (Swinbank and Ortland, 2003) wind climatology. Also on UARS, the limb-sounding WIND Imaging Interferometer (WINDII) observed O( 1 S) airglow emission to measure winds over 90-110 km (Gault et al, 1996b). Since 2002 the TIMED Doppler Interferometer (TIDI) has been making limb-scanning measurements of O( 1 S) and O 2 (0-0) band emissions for determining horizontal winds above 60 km (Killeen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Over a 14-year period the space-borne high-resolution Doppler imager (HRDI) (Burrage et al, 1996) measured wind velocities typically between 60 • N and 60 • S and down to 50 km and contributed to the Upper Atmosphere Research Satellite (UARS) Reference Atmosphere Project (URAP) (Swinbank and Ortland, 2003) wind climatology. Also on UARS, the limb-sounding WIND Imaging Interferometer (WINDII) observed O( 1 S) airglow emission to measure winds over 90-110 km (Gault et al, 1996b). Since 2002 the TIMED Doppler Interferometer (TIDI) has been making limb-scanning measurements of O( 1 S) and O 2 (0-0) band emissions for determining horizontal winds above 60 km (Killeen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These temperatures correspond to an integration of the emission along the lines-of-sight. The last step consists of the inversion of these apparent quantities to obtain a temperature profile as a function of altitude, as described for wind measurements by Gault et al (1996). The detailed description of the inversion technique has been given by Rochon (2000).…”
Section: Doppler Temperature Retrievalmentioning
confidence: 99%
“…The performance of the instrument over time has been described by Thuillier et al (1998). Although the wind measurements in the O( 1 S) and O( 1 D) emissions have been validated by comparisons with measurements by other instruments (Gault et al, 1996;Thuillier et al, 1996;Lathuillère et al, 1997), the Doppler temperatures have never been validated. The purpose of the present study is to examine several aspects of the WINDII daytime O( 1 D) temperature measurements to determine what level of confidence to place in them as indicators of atmospheric temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The validation of the WINDII green-line wind observations (Gault et al, 1996) has taken a similar approach to that used for the HRDI MLT winds. In the comparisons of HRDI and WINDII observations with other techniques, it was found that medium-frequency (MF) radars can significantly underestimate the wind speeds in the mesosphere and lower thermosphere (MLT) region Gault et al, 1996;Khattatov et al, 1996). Since until the launch of UARS MF radars were the primary source of wind information, reference models also contain these biases (Fleming et al, 1996).…”
Section: Introductionmentioning
confidence: 99%